Elucidation of roles for vitamin B 12 in regulation of folate, ubiquinone, and methionine metabolism - Romine, Margaret F; Rodionov, Dmitry A; Maezato, Yukari; Anderson, Lindsey N; Nandhikonda, Premchendar; Rodionova, Irina A; Carre, Alexandre; Li, Xiaoqing; Xu, Chengdong; Clauss, Therese R W; Kim, Young-Mo; Metz, Thomas O; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Only a small fraction of vitamin B -requiring organisms are able to synthesize B de novo, making it a common commodity in microbial communities. Initially recognized as an enzyme cofactor of a few enzymes, recent studies have revealed additional B -binding enzymes and regulatory roles for B Here we report the development and use of a B -based chemical probe to identify B -binding proteins in a nonphototrophic B -producing bacterium. Two unexpected discoveries resulted from this study. First, we identified a light-sensing B -binding transcriptional regulator and demonstrated that it controls folate and ubiquinone biosynthesis. Second, our probe captured proteins involved in folate, methionine, and ubiquinone metabolism, suggesting that it may play a role as an allosteric effector of these processes. These metabolic processes produce precursors for synthesis of DNA, RNA, and protein. Thereby, B likely modulates growth, and by limiting its availability to auxotrophs, B -producing organisms may facilitate coordination of community metabolism.